Cholinergic Actions of Autoantibodies from Breast Cancer Patients on Dendritic Cells - Lombardi, María Gabriela (2015)
Autoantibodies (autoAbs) against self-proteins have been localized in tumor microenvironment exerting acomplex network of interactions. We reported the presence of autoAbs in breast cancer patients, which promotetumor progression by activating muscarinic acetylcholine receptors (mAChR) in tumor cells. Cholinergic receptorsare also expressed in dendritic cells (DC) and much clear evidence demonstrated a deficient functional activity ofDC in cancer. Here we investigated whether autoAbs can modulate the expression of maturation markers and theproduction of cytokines by DC. IgG from breast cancer patients in stage I reduced the expression of HLA-DR andCD86 as well as tumor necrosis factor alpha liberation and augmented interleukin IL-12 and IL-10 levels bycholinergic activation of mature DC. The latter cytokines are also up-regulated in patients? sera, probably due totumor influence, since the addition of breast tumor extract increased cytokine levels in immature DC reaching levelsof mature DC mainly for IL-10 and IL-12. It could be assumed that autoAbs are reinforcing the tolerogenic/immunosuppressive profile mediated by DC in breast cancer.